PENERAPAN METODE SYSTEM DEVELOPMENT LIFE CYCLE PADA PEMBUATAN SISTEM INFORMASI PENJUALAN PRODUK BATIK KUROWO JAKARTA - Wulan Dari (Jurnal Khatulistiwa Informatika, 2015)
Technological developments can assist in designing an e-commerce store Batik Kurowo, where e-commerce system designed to support the functioning sales system running. The methodology used is the System Development Life Cycle (SDLC) with a role in several stages of web information system builders such as planning systems, systems analysis, design / system design, application / system implementation and system maintenance. In the process of marketing and selling batik products Kurowo has disadvantages, namely the difficulties in marketing their products. The result achieved is an online sales web-based application that can simplify customer Kurowo Batik shop in purchase transactions.Keywords: Sales, Internet, batik products, batik Kurowo